Understanding the Nagorno-Karabakh conflict: domestic politics and twenty-five years of fruitless negotiations 1994–2018. Issue 3 (2nd September 2019) - Gasparyan, Arsen
ABSTRACT: The Nagorno-Karabakh conflict negotiations have been continuing for more than two decades now, but a settlement still remains elusive. This paper is an exploration of the reasons for that failure, and it argues that the real obstacle for the peaceful settlement in Nagorno-Karabakh was the domestic politics of the parties to the conflict. By clarifying and testing alternative perspectives, this paper seeks to resolve an important debate about the causes of the OSCE Minsk process failure.